Analysis of Effect of Financial Performance Against Disclosure of Corporate Social Responsibility (CSR) and foreign capital ownership as a moderating variable - Amelia Ika Pratiwi (Jurnal VOK@SINDO, 2015)
This study aims to analyze and determine the effect of financial performance against disclosure of Corporate Social Responsibility (CSR), examine and provide an overview Of Corporate Social Responsibility disclosure in the Indonesian mining industry, especially with the influence of foreign capital ownership as a moderating variable. The population in this study is all mining companies listed in Indonesia Stock Exchange 2011-2013 period using purposive sampling method. Data analysis method used is the analysis of financial ratios, among others, Return on Assets (ROA), Leverage, Current Ratio (CR), and holdings of foreign capital. The result shows that financial performance does not significantly influence the disclosure of Corporate Social Responsibility (CSR) and foreign capital ownership as moderating variables also has no significant effect on the financial performance and disclosure of Corporate Social Responsibility (CSR).